2015
DOI: 10.1177/1751143714564816
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic considerations and dosing strategies of antibiotics in the critically ill patient

Abstract: The treatment of sepsis remains a significant challenge and is the cause of high mortality and morbidity. The pathophysiological alterations that are associated with sepsis can complicate drug dosing. Critical care patients often have capillary leak, increased cardiac output and altered protein levels which can have profound effects on the volume of distribution (Vd) and clearance (Cl) of antibacterial agents, both of which may affect the pharmacokinetics (PK) / pharmacodynamics (PD) of the drug. Along with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…The misuse of antimicrobial medicines accelerates the natural evolution of resistant strains and encourages the spread of AMR. Previous studies have reported that therapeutic failure and negative clinical outcomes emanate from subtherapeutic doses of antibiotics, which leads to the development of antibiotic resistance if suitable adjustments to the dose are not made (Shah et al, 2015, Roberts et al, 2008. In today's clinical trials, biochemical and genetic mechanisms of resistance are demonstrated by most bacterial strains.…”
Section: Introductionmentioning
confidence: 99%
“…The misuse of antimicrobial medicines accelerates the natural evolution of resistant strains and encourages the spread of AMR. Previous studies have reported that therapeutic failure and negative clinical outcomes emanate from subtherapeutic doses of antibiotics, which leads to the development of antibiotic resistance if suitable adjustments to the dose are not made (Shah et al, 2015, Roberts et al, 2008. In today's clinical trials, biochemical and genetic mechanisms of resistance are demonstrated by most bacterial strains.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic target sites[8].Pharmacokinetics (PK) refers to the study of concentration changes of a drug over a period of time. After the administration of a drug, drugs undergoes ADME (absorption, distribution, metabolism and excretion) processes that condition the kinetics of the drug and the concentration-time profile, which may be characterized by the PK parameters, such as total body clearance, volume of distribution, protein binding or bioavailability[30,31].Pharmacokinetics of antibioticsAminoglycosides route of administered is majorly via parenteralexcept cases of intestinal infections or indication for decontamination. aminoglycosides upon absorption into the bloodstream, they have low volume of distribution (<0.3 L/kg) thus aminoglycosides are mainly distributed in blood plasma.…”
mentioning
confidence: 99%
“…34,35 Therefore, obese individuals may have poorer peripheral perfusion, resulting in lower subcutaneous adipose tissue concentrations of antimicrobials. 35 Oedema combined with fluid resuscitation in critically ill obese patients can further increase the Vd of different antimicrobials 14 (Figure 2-2).…”
Section: Effects Of Obesity On Drug Distributionmentioning
confidence: 99%
“…7 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (n = 38) Of interest, the statistical significance of obesity for affecting PK/PD target attainment for piperacillin in the univariate analysis was not found to be significant in the logistic regression (Table 3 -5). The factors associated with achieving the lower PK/PD target, 100% fT>MIC, for both antibiotics included use of prolonged infusion, a lower CLCR defined as ≤ 100 mL/min and increasing age.…”
Section: Clcr > 50 To ≤ 100mentioning
confidence: 99%
See 1 more Smart Citation